COVID-19 crisis, MSMEs resilience, and the role of ICT: A preliminary investigation in rural Bantul, Indonesia - Amri Ikhwan; Amrullah Satrio; Sulistiyo Sigit; Widyaningsih Anastasia Endar; Hikmasari Bella Sinta; Nababan Cornelius Antoni; Wijayanti Dessy Ayu; Ruslanjari Dina (E3S Web of Conferences, 2023)
The COVID-19 pandemic triggered widespread economic instability on a global scale, affecting micro, small, and medium-sized enterprises (MSMEs) as well. This paper presents an initial investigation conducted in Sriharjo, a rural area in Bantul Regency, Indonesia, to explore the resilience of MSMEs and the role of information and communication technology (ICT) in supporting their operations. Eight key informants, including a village-owned enterprise (VOE) manager, an online marketplace website administrator, and six traditional food and beverage MSME owners, were interviewed at the end of 2022. The outbreak prevention policies disrupted economic activities in Sriharjo, prompting the VOE to initiate specific strategies, such as business digitalization, to mitigate the economic impact. MSME owners employed various coping strategies during the crisis, leading to diverse outcomes during the recovery phase, with some experiencing further decline while others rebounded successfully. However, ICT utilization remained limited among the investigated MSMEs, despite the village government's early digitalization initiatives. To enhance business agility and scalability, comprehensive strategies must be designed to strengthen their digital capabilities in response to unpredictable changes.